1990
DOI: 10.1016/0014-5793(90)81408-g
|View full text |Cite
|
Sign up to set email alerts
|

A high ratio of chromogranin A to synaptin/synaptophysin is a common feature of brains in Alzheimer and Pick disease

Abstract: Chromogranin A and synaptin/synaptophysin were characterized by immunological methods in human autopsy brain tissue from patients with Alzheimer's and Pick's disease. In immunoblots there was no qualitative difference between the antigens in control and diseased brain, but significant quantitative differences were found. In all Alzheimer cases there was a significantly lower level of synaptin/synaptophysin, whereas chromogranin A was higher in 4 out of 5 cases and in all cases relative to synaptin/synaptophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 28 publications
(29 reference statements)
2
28
0
1
Order By: Relevance
“…31,33) CgA is also reported to accumulate in patients with Parkinson's disease and Pick's disease. [34][35][36] O-Glycosylation of a-synuclein is reported as well.…”
Section: Discussionmentioning
confidence: 81%
“…31,33) CgA is also reported to accumulate in patients with Parkinson's disease and Pick's disease. [34][35][36] O-Glycosylation of a-synuclein is reported as well.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have shown that in addition to these traditionally described lesions, AD is characterized by selective neuronal loss [30,72], severe and early loss of synapses [15,16,24,45,59], and synaptic pathology [41,44]. Early immunocytochemical studies indicated an average 45% decrease in presynaptic terminal density in the AD neocortex [44,45,76]. Quantitative morphometric study of temporal and frontal cortical biopsies performed within an average of 2 to 4 years from the onset of clinical AD revealed 25 to 35% decrease in the numerical density of synapses and 15 to 35% decrease in the number of synapses per cortical neuron [15].…”
Section: Introductionmentioning
confidence: 99%
“…CrA is present in the brain, where the concentration is highest in the neocortex [11], while it is not found in the white matter [12,13]. Immunohistochemically, CrA is found in a granular distribu tion in the neuronal perikarya, dendrites, and synapses [12][13][14], a distribution consistent with a location in the large dense-core synaptic vesicles, which has been con firmed ultrastructurally [15][16][17],…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CrA is found in senile plaques [18,19], especially in such with a neuritic component [13,14], although also present in diffuse (3A4 amyloid deposits (diffuse plaques) [20], and in a recently described type of lesion, tangle-associated neuritic clusters, composed of aggregates of abnormal neurites centred by an extracellu lar NFTs [ 19],…”
Section: Introductionmentioning
confidence: 99%